Transgender Therapy, Social Justice, and the Northern Context: Challenges and Opportunities - Neufeld, Angela C. (Canadian Journal of Counselling and Psychotherapy, 2014)
Gender remains one of the most persistent and all-encompassing binary systems of classifying people. As a result, transgender individuals experience widespread prejudice and discrimination and experience higher rates of mental disorders and suicide. With a case study as illustration, the value of social justice in transgender therapy is explored. Attention is paid to how social justice practices support therapists in being mindful of the intersection of identities and to why such practices are critical in supporting the mental health of transgender clients in northern Canada. Recommendations for social-justice informed transgender therapy are discussed.